INTEGRATING OIDDE-BASED CONTEXTUAL MODULES INTO VIRUS INSTRUCTION: EFFECTS ON CONCEPTUAL UNDERSTANDING AND STUDENT ENGAGEMENT IN SECONDARY BIOLOGY EDUCATION - Eka Bintarawati; Rr. Eko Susetyorini; Abdulkadir Rahardjanto; Atok Miftachul Hudha; Husamah Husamah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This research is motivated by the high demands for student-centered learning in the 21st century, while the teaching of viruses at the secondary school level is still dominated by conventional memorization-oriented methods without linking abstract concepts to contextual scientific problems. The focus of this research problem is directed at testing the effectiveness of a contextual teaching module based on the OIDDE (Orientation, Identify, Discussion, Decision, and Engage in Behavior) model on improving students' conceptual understanding. Using a quantitative approach with a quasi-experimental design in the form of a pretest-posttest control group design, the research's key stages were carried out in a structured manner through purposive sampling involving 70 10th-grade students at SMAN 2 Sampit. The experimental group received instruction using the OIDDE-based module, while the control group received conventional instruction. Quantitative data were collected using a multiple-choice test and analyzed inferentially through ANCOVA, N-Gain scores, and Cohen's d. The research findings showed that the experimental group achieved an average post-test score of 87.00, significantly exceeding the control group, which scored 73.86 based on the ANCOVA analysis (p < 0.05). The learning improvement was categorized as moderate, with an N-Gain value of 0.6466 and a Cohen's d effect size of 2.916, which is considered very strong. The main conclusion confirms that the integration of OIDDE-based contextual modules has proven effective and significantly improves students' conceptual understanding in teaching viruses. ABSTRAK Penelitian ini dilatarbelakangi oleh tingginya tuntutan pembelajaran berpusat pada siswa di era abad ke-21, sementara pengajaran materi virus di tingkat sekolah menengah masih didominasi metode konvensional berorientasi hafalan tanpa mengaitkan konsep abstrak dengan masalah ilmiah kontekstual. Fokus masalah riset ini diarahkan pada pengujian efektivitas modul ajar kontekstual berbasis model OIDDE (Orientation, Identify, Discussion, Decision, and Engage in Behavior) terhadap peningkatan pemahaman konseptual para siswa. Menggunakan pendekatan kuantitatif dengan desain eksperimen semu berbentuk pretest-posttest control group design, tahapan penting penelitian dijalankan secara terstruktur melalui purposive sampling yang melibatkan 70 siswa kelas X di SMAN 2 Sampit. Kelompok eksperimen mendapatkan pengajaran memanfaatkan modul berbasis OIDDE, sedangkan kelompok kontrol menerima instruksi konvensional. Data kuantitatif dihimpun menggunakan tes pilihan ganda yang dianalisis secara inferensial melalui uji ANCOVA, skor N-Gain, dan Cohen’s d. Temuan penelitian menunjukkan bahwa kelompok eksperimen meraih skor rata-rata pascatest sebesar 87,00, secara signifikan melampaui kelompok kontrol yang memperoleh skor 73,86 berdasarkan hasil analisis ANCOVA (p < 0,05). Peningkatan pembelajaran berada pada kategori sedang dengan nilai N-Gain sebesar 0,6466 serta ukuran efek Cohen’s d sebesar 2,916 yang tergolong sangat kuat. Simpulan utama menegaskan bahwa integrasi modul kontekstual berbasis OIDDE terbukti efektif dan signifikan meningkatkan pemahaman konseptual peserta didik pada pengajaran materi virus.